2004
DOI: 10.1203/01.pdr.0000128981.38670.28
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Maternal Fluoxetine Infusion in Pregnant Sheep: Effects on the Maternal and Fetal Hypothalamic-Pituitary-Adrenal Axes

Abstract: Depression during pregnancy is frequently treated with the selective serotonin reuptake inhibitor, fluoxetine (FX). FX increases serotonergic neurotransmission and serotonin plays a role in the regulation of the hypothalamic-pituitary-adrenal (HPA) axis. We have therefore investigated the effect of chronic administration of FX to the pregnant ewe on the maternal and fetal HPA axes. Nineteen late-gestation sheep were surgically prepared for chronic study of the fetus. FX (n ϭ 7, 98.5 g/kg/d) or sterile water (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 42 publications
3
23
0
Order By: Relevance
“…Continuous infusion of fluoxetine in sheep via maternal femoral vein catheter yielded concentrations in maternal and fetal serum of ;150 and ;60 ng/ml, respectively; no measurements of norfluoxetine were obtained (Morrison et al, 2004). Similar results were found in mice: placental transfer of fluoxetine was 69%, whereas human placental transfer is 73% (Noorlander et al, 2008).…”
Section: Selective Serotonin Reuptake Inhibitor Antidepressant Anisupporting
confidence: 60%
“…Continuous infusion of fluoxetine in sheep via maternal femoral vein catheter yielded concentrations in maternal and fetal serum of ;150 and ;60 ng/ml, respectively; no measurements of norfluoxetine were obtained (Morrison et al, 2004). Similar results were found in mice: placental transfer of fluoxetine was 69%, whereas human placental transfer is 73% (Noorlander et al, 2008).…”
Section: Selective Serotonin Reuptake Inhibitor Antidepressant Anisupporting
confidence: 60%
“…To distinguish acute pharmacological effects from long-term sustained outcomes, we examined fetal blood flow and fHR variability measures before a typical morning SSRI dose (trough) and during an afternoon postdose (peak) session. Given, previous reports of neonatal cardiorespiratory and neurobehavioral disturbances in our sheep model after prenatal SSRI exposure (15)(16)(17), we expected blunted fetal brain blood flow indices and heart rate variability during late gestation would be present during both trough (predose) and peak (1-2 h postdose) drug conditions, reflecting sustained fetal effects rather than an acute pharmacological effect.…”
mentioning
confidence: 81%
“…In pregnant sheep, an 8-d i.v. fluoxetine infusion resulted in initial transient reductions in uterine blood flow and fetal oxygenation, prolonged reduction in fetal rapid eye movement (REM) sleep, and augmented prepartum cortisol increase (15)(16)(17). Altered fetal REM sleep could affect cerebral blood flow and metabolism via changes between quiet and REM sleep which may in turn have long-term effects on brain growth and maturation (18).…”
mentioning
confidence: 99%
“…Some studies noted decreased values of these parameters (18 -21), whereas others did not (1,2,5). Growth attenuation accompanied by impaired growth hormone (GH) secretion was also reported in four children and adolescents treated with SSRIs for various psychiatric disorders (22).Insulin-like growth factor-I (IGF-I), a GH-dependent hormone, is known to play a major role in fetal growth (23,24), but there is limited information on the response of the fetal IGF-I/GH axis to maternal SSRI intake, or the response of the fetal hypothalamic-pituitary-adrenal (HPA) axis, which is involved in serotonin regulation of cortisol and adrenocorticotropic hormone (ACTH) secretion (25)(26)(27). In a sheep model, fetal plasma ACTH and cortisol significantly increased after chronic maternal fluoxetine administration (26), raising concerns of fetal exposure to excess glucocorticoids at critical periods during development.…”
mentioning
confidence: 99%
“…In a sheep model, fetal plasma ACTH and cortisol significantly increased after chronic maternal fluoxetine administration (26), raising concerns of fetal exposure to excess glucocorticoids at critical periods during development. Human epidemiologic observations and animal studies have shown that under suboptimal in utero conditions, individual tissues and organ systems can be programmed, with adverse consequences for their function in later life (28 -30).…”
mentioning
confidence: 99%